Globalisation of sports - Alexander Dilger (Westfälische Wilhelms-Universität Münster, Institut für Organisationsökonomik, 2023)
Globalisation affects not only politics and the economy, but also sport, which has become significantly more international, competitive and financially powerful. This is particularly advantageous for most consumers or spectators. Especially top athletes benefit, while not so good athletes can suffer from the greater competitive pressure. The same applies to event organisers and the mass media, from which the best and largest in particular benefit. Poorer nations can more easily enter and win international competitions, although richer nations retain advantages. All in all, globalisation of sports is not a zero-sum game, but the benefits outweigh the costs. – – Die Globalisierung betrifft nicht nur Politik und Wirtschaft, sondern auch den Sport, der viel internationaler, kompetitiver und finanzkräftiger geworden ist. Das ist insbesondere für die meisten Konsumenten bzw. Zuschauer von Vorteil. Auch Spitzensportler profitieren, während nicht ganz so gute Athleten unter dem größeren Wettbewerbsdruck leiden können. Dasselbe gilt für Veranstalter und Massenmedien, von denen vor allem die besten und größten profitieren. Ärmere Nationen können leichter an internationalen Wettbewerben teilnehmen und auch gewinnen, wenngleich reichere Nationen Vorteile behalten. Insgesamt handelt es sich nicht um ein Nullsummenspiel, sondern überwiegen die Vorteile der Globalisierung des Sports.
Keywords: F69; L83; Z20; 650; Competition; Globalisation; Media; Olympics; Sports